2022
DOI: 10.3390/biomedicines10071464
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response to SARS-CoV-2 Vaccines

Abstract: COVID-19 vaccines have been developed to confer immunity against the SARS-CoV-2 infection. Prior to the pandemic of COVID-19 which started in March 2020, there was a well-established understanding about the structure and pathogenesis of previously known Coronaviruses from the SARS and MERS outbreaks. In addition to this, vaccines for various Coronaviruses were available for veterinary use. This knowledge supported the creation of various vaccine platforms for SARS-CoV-2. Before COVID-19 there are no reports of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 155 publications
0
32
0
Order By: Relevance
“…It is possible to measure the protective effectiveness of antibodies and the success of humoral immune responses following vaccination by measuring the titers of SARS-CoV-2 anti-spike IgG antibodies [ 34 ]. Janssen vaccine has showed 72% efficacy in the USA, 66% efficacy in Latin America, and 57% documented efficacy in South Africa [ 35 ]. The same study also showed that the efficacy of Janssen vaccine can be boosted to 77% efficacy 14 days post-immunization and 85% after 28 days.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to measure the protective effectiveness of antibodies and the success of humoral immune responses following vaccination by measuring the titers of SARS-CoV-2 anti-spike IgG antibodies [ 34 ]. Janssen vaccine has showed 72% efficacy in the USA, 66% efficacy in Latin America, and 57% documented efficacy in South Africa [ 35 ]. The same study also showed that the efficacy of Janssen vaccine can be boosted to 77% efficacy 14 days post-immunization and 85% after 28 days.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 Once the mRNA vaccine encapsulated in lipid nanoparticles is taken up by human cells, such as dendritic cells or myocytes, it is translated into a viral spike protein antigen that stimulates B cells to produce a neutralizing antibody (nAb) against the spike protein, which prevents viral infection and also induces cytotoxic T cells that acquire the ability of cellular immune responses against infected cells. 3 , 4 Therefore, immunocompromised patients and patients receiving treatment with an immunosuppressive moiety are generally at high risk for impaired antibody response against anti–SARS-CoV-2 vaccination. 5 , 6 Among the various settings of immunosuppressive treatment, therapeutic approaches that deplete B cells or impair B-cell function, such as an anti-CD20 monoclonal antibody (MoAb) or inhibitors for B-cell receptor signaling, have especially attracted attention as risk factors for severe COVID-19 in patients with B-cell malignancies, including B-cell lymphomas (BCLs) and chronic lymphocytic leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…The spike (S) protein of the virus, which contains the major neutralizing epitopes in the receptor binding domain (RBD) and N-terminal domain (NTD), has proved to be the most promising immunogen (18). Thus, most of the recently approved vaccines employ full-length S (with or without modification) or whole virus (inactivated) as a target antigen (19). titers 100TCID50 for the micro-VNT50 assay.…”
Section: Introductionmentioning
confidence: 99%